1998
DOI: 10.1152/jn.1998.80.1.130
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Signs of the Activation of Bag2 and Chain Intrafusal Muscle Fibers of Gastrocnemius Muscle Spindles in the Cat

Abstract: A method is described for identifying the effect of single gamma static (gamma(s)) axons on bag2 or chain intrafusal fibers using random (Poisson-distributed) stimuli. The cross-correlogram of the stimuli with the firing of spindle primary afferents took one of three forms. A large, simple, brief response was taken to indicate pure chain fiber activation and a small, prolonged response to indicate pure bag2 activation. A compound response with brief and prolonged components was taken to be a sign of mixed inne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 17 publications
0
38
2
Order By: Relevance
“…First, the decreased depth of modulation of discharge associated with increased activity during muscle shortenings and increased variability of the instantaneous frequency of discharge, which might also be concomitant with altered spontaneous activities, seem to be related to a static fusimotor drive (for review, see Hulliger, 1984;Prochazka, 1996). The effects observed, in particular the biasing effect, were neither as frequent nor as powerful as expected from animal data (Celichowski et al, 1994;Taylor et al, 1998;Durbaba et al, 2001). This difference may be explained by the natural condition of ␥ driving in the present study compared with the electrical stimulation used in animal experiments.…”
Section: Nature Of the Fusimotor Effectscontrasting
confidence: 76%
“…First, the decreased depth of modulation of discharge associated with increased activity during muscle shortenings and increased variability of the instantaneous frequency of discharge, which might also be concomitant with altered spontaneous activities, seem to be related to a static fusimotor drive (for review, see Hulliger, 1984;Prochazka, 1996). The effects observed, in particular the biasing effect, were neither as frequent nor as powerful as expected from animal data (Celichowski et al, 1994;Taylor et al, 1998;Durbaba et al, 2001). This difference may be explained by the natural condition of ␥ driving in the present study compared with the electrical stimulation used in animal experiments.…”
Section: Nature Of the Fusimotor Effectscontrasting
confidence: 76%
“…It has been shown that a substantial part of the γ s motor output during locomotion in the cat fluctuates with a smoothly modulated pattern that resembles the profile of muscle shortening (Murphy et al . 1984; Taylor et al . 2000 a , b ) and acts to oppose the unloading effect of shortening.…”
mentioning
confidence: 99%
“…2000 a , b ) and acts to oppose the unloading effect of shortening. For this reason it may be better to regard the γ s pattern as a signal that is algebraically summed with muscle length to determine the afferent firing, rather than as a means of controlling the sensitivity of the spindle to stretch (see Taylor et al . 2000 a,b ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both groups also used random length inputs, and confined their attention to single static fusimotor fibres. The only remaining instances of random, or pseudorandom, fusimotor stimulation that have come to our attention, once again using single static fibres but with the muscle held at constant length, were concerned with the problem of identifying the type, or types, of intrafusal muscle fibre activated in each case (Taylor et al, 1998;Petit et al, 1999).…”
Section: Discussionmentioning
confidence: 99%